Antibiofilm of Arumanis Mango Leaves (Mangifera indica L.) Ethanol Extract Against Staphylococcus aureus in vitro - Hepziba, Evangelista Rachel; Soesanto, Sheila; Widyarman, Armelia Sari (Indonesian Dental Association, 2022)
Introduction: Staphylococcus aureus is a pathogen bacteria that forms biofilm and induces acute inflammation associated with dentoalveolar abscess, which needs antibiotics such as amoxicillin for the treatment. Due to antibiotic resistance and various side effects, natural ingredients are needed as an alternative treatment. Arumanis mango leaves (Mangifera indica L.) contains mangiferin, flavonoid, and tannin which are expected to inhibit the growth of Staphylococcus aureus and its biofilm formation. Objective: The aim of this study was to determine the antibacterial and antibiofilm effects of Mangifera indica L. leaves against Staphylococcus aureus in vitro. Methods: This study was in vitro laboratory experiment with post test only control group design. Antibacterial test was carried out by plate count method and antibiofilm test was carried out by microtiter plate biofilm assay method. Staphylococcus aureus ATCC 25923 was cultured in BHI broth in 37oC for 24h with anaerobic condition. The present study used ethanol extract of Mangifera indica L. leaves in 6 different concentrations: 3,125%, 6,25%, 12,5%, 25%, 50%, and 100%. Amoxicillin was used as positive control and DMSO 10% used as negative control. Data was analyzed with Shapiro-wilk test, One-way ANOVA test, and post hoc Tukey HSD test with p<0,05 as the level of significance. Results: The most effective concentration to inhibit the growth of Staphylococcus aureus was 100% extract compared to negative control (p<0,05). The most effective concentration against Staphylococcus aureus biofilm formation was 100% extract in 3hr incubation compared to negative control (p<0,05). Conclusion: Ethanol extract of Mangifera indica L. leaves has been shown in vitro to have antibacterial and antibiofilm properties against Staphylococcus aureus.